Coastal Vulnerability Assessment Along The North Java Coastlines-Indonesia - Aida Heriati; Fitry Suciaty; Dian N. Handiani (Jurnal Segara, 2022)
The north coast of Java is an area with very diverse maritime activities. These high activities threaten the ecosystem and environmental sustainability. Several areas already experience environmental degradation and most of the threats come from ocean pollution, coastal erosion, continuous tidal flood (rob), and coastal land subsidence. Furthermore, the coastal degradation is worsened by climate change which may cause the area more vulnerable to disaster. This study aims at evaluating the coastal vulnerability using weighted coastal vulnerability index (CVIw). The method calculates coastal vulnerability by weighting physical coastal parameters using Analytical Hierarchy Process (AHP). CVIw calculation result shows that the vulnerability is dominant at high (39%) and very high (51%) classes. The high vulnerability occurs in Tangerang, Bekasi, Brebes, Demak, Jepara, Pati, and Rembang Regencies. Meanwhile, very high vulnerability takes place in several regencies: Serang, Karawang, Subang, Indramayu, Cirebon, Tegal, Kendal, Semarang, and Gresik. The parameters of relief, coastal features, tidal range and shoreline give contribution more in coastal vulnerability besides lithology, sea level change, and wave height. Identifying vulnerability in these areas might help local governments to prioritize their action plan in coastal disasters mitigation.